Analisis terhadap elemen Maqasid al-Syariah dalam produk Takaful Ikhlas di Malaysia / Arif Fathillah Mohd Safar - Arif Fathillah , Mohd Safar (2011)
This research is done to identify the existence of maqasid al-Shari‘ah element in the products of Family Takaful under Takaful Ikhlas Sdn. Bhd. To fulfill the goal, research has been done on the interest, terms and condition that are applied in the Family Takaful products. Information regarding the benefits and term and condition of the product has been obtained through interviews, Family Takaful certificates, products brochures, official web page of Takaful Ikhlas Sdn. Bhd., and the Ikhlas Care service. Among the outcome of the research is Family Takaful products that is offered by Takaful Ikhlas Sdn. Bhd. which contain the elements of maqasid al-Shari‘ah in terms of the preservation towards the five basic importance (al-daruriyyat al-khams) which are religion, spirit, state of mind, family desendence and property. Apart from that, this research also found that the Family Takaful products which is offered by Takaful Ikhlas Sdn. Bhd. may reduce the burden from the participant, prevent loss, provide proper judgement and happiness as wanted by Islam. However the reseacrh has identified that the renewal towards the benefits, terms and conditions of several products needs to be done so that maqasid al-Shari‘ah can be achieved and realised in its true meaning. Therefore, several suggestion has been proposed to the relevant bodies in order to overcome the weakness and enhance the quality of the product.